Moderasi Pendidikan Islam dan Tantangan Masa Depan - Hanifatulloh, Bayu Alif Ahmad Yasin (Tsamratul Fikri | Jurnal Studi Islam, 2020)
This study aims to elaborate on the moderation of education and the challenges of education in the future. This study uses literature study method. The results of the study show that students are a group that is very vulnerable to being carried away by the flow of religious radicalism. A very young age and considered to be unstable, with a passionate spirit, and a strong desire to enforce religious teachings more comprehensively makes this young group who is within the scope of an educational institution to become the most vulnerable social group to be infiltrated and become the target of radical groups that convey religious understandings and attitudes that are rigid and tend to be superficial. On the other hand, new challenges have begun to emerge, such as advances in science and technology, democratization, and moral decadence that have surrounded human life in this era. So a special strategy is needed to be able to instill moderate Islamic values ​​in students by utilizing teaching and learning activities and parenting patterns that exist in the community or in educational institutions. Because Islamic educational institutions have a moral and social burden to participate in finding the right solution or solution in order to prepare superior human resources who have strong competitiveness for the advancement and harmony of religion, nation and state.